Treatment of systemic sclerosis-associated digital ulcers: Recommendations of the Turkish Society for Rheumatology - (:unkn) unknown (My University, 2023)
OBJECTIVES: Digital ulcers (DUs) are associated with a significant burden in systemic sclerosis (SSc) by leading to severe pain, physical disability, and reduced quality of life. This effort aimed to develop recommendations of the Turkish Society for Rheumatology (TRD) on the management of DUs associated with SSc. METHODS: In the first meeting held in December 2020 with the participation of a task force consisting of 23 rheumatologists the scope of the recommendations and research questions were determined. A systematic literature review was conducted by 5 fellows and results were presented to the task force during the second meeting. The Oxford system was used to determine the level of evidence. The preliminary recommendations were discussed, modified, and voted by the task force and then by members of TRD via e-mail invitation allowing personalised access to a web-based questionnaire [SurveyMonkey®]. RESULTS: A total of 23 recommendations under 7 main headings were formulated covering non-pharmacological measures for the prevention of DUs and pharmacological treatments including vasodilators, anti-aggregants, antibiotics, wound care, pain control, and interventions including sympathectomy, botulinum toxin, and surgery. Risk factors, poor prognostic factors, prevention of DU and adverse effects of medical treatments were reported as 4 overarching principles. CONCLUSIONS: These evidence-based recommendations for the management of SSc-associated DUs were developed to provide a useful guide to all physicians who are involved in the care of patients with SSc, as well as to point out unmet needs in this field.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; İmmünoloji ve Romatoloji; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Medicine; Internal Medicine Sciences; Internal Diseases; Immunology and Rheumatology; Life Sciences; Health Sciences; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; İmmünoloji; ALERJİ; ROMATOLOJİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; IMMUNOLOGY; ALLERGY; RHEUMATOLOGY; Romatoloji; İmmünoloji ve Alerji; Rheumatology; Immunology and Allergy; Immunology